A Emprical Study on Pre and Post Covid Hr Practices in it Industry with Special Reference to Bangalore - A.Manojkumar; Annisha (PT FORMOSA CENDEKIA GLOBAL, 2022)
Because of the increasing epidemic, many countries around the world have used lock lockdowns to overcome the deathly impact of the pandemic. This was aimed at locking billions of citizens out of their homes, leading to home-based work - new ones, and taking businesses to ensure security. As a result, the global economy is expected to fall by more than 3% by 2020 - the strongest decline since the Great Depression of the 1930s, according to the International Monetary Fund (IMF). While a recent (pre-Covid) report from Nasscom indicated that the IT sector in India would grow 7.7% in revenue, another report (during Covid) from Gartner indicated that India's IT & ITeS services industry would see 8% decline by 2020. Globally, the IT industry shifted gears to embrace change and was forced to rethink strategies. While the scar will take some time to heal, the IT industry is well prepared to lead and ensure that return to business is much safer.